If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -2 = 13 Reorder the terms: -2 + 6y = 13 Solving -2 + 6y = 13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 6y = 13 + 2 Combine like terms: -2 + 2 = 0 0 + 6y = 13 + 2 6y = 13 + 2 Combine like terms: 13 + 2 = 15 6y = 15 Divide each side by '6'. y = 2.5 Simplifying y = 2.5
| -x^2-40x-80=0 | | -3=8(3)+9 | | 6-4(3x-1)=-26 | | 11x^2=26x-x^3 | | 1=3(3)+9 | | 3=1(3)+9 | | 7x^2-4+7x-9x^2-4x= | | 14x+4y=24 | | 6-x=2x-12 | | 47=4x-5 | | 7x+33-x=3x+39 | | =9b^2-48b+64 | | -x^2+x-4+2x+-x^2= | | 2=3(2)+9 | | 2(s-4)7=-19 | | 4-6=2x-2 | | 4p-5q=29 | | 9c-11=c+25 | | 5x+155=11x-13 | | 0.4x-1.8=-3.7 | | 6x-19x=0 | | 3x-7x+12=32 | | (-4+8x)=6 | | =4x^2-19xy-5y^2 | | y=-(2/3)40+30 | | y=-(2/3)20+30 | | -3(4b-10)=.50(-24b+60) | | y=-(2/3)15+30 | | 3x+4(x-5)=1 | | -2=x^2-4x-5 | | y=-1*-1+-1 | | 2n+7=2n+12 |